Peralihan Hak Atas Tanah Warisan yang Sedang Dibebani Hak Tanggungan - Eko Irawan (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Abstract: This paper aims to analyze a legal event of transfer of inheritance land under burden of Mortgage; obstacles faced by the debtor in relation to the transfer of rights to inheritance land still burdened by the mortgage; and legal consequences if the beneficiary rejects the inheritance of land rights that are being borne by the mortgage. The end of this paper concludes three things. First, that the procedure for the transfer of rights to inheritance land that is being burdened by the mortgage right is executed after obtaining written approval from the holder of the mortgage or other party authorized to approve the removal of the burden in question. Also, the registration of the transfer of mortgages is done by recording it on the land books as well as the certificates of the related mortgages and on the land books and certificates of the rights imposed on the basis of a certificate of transfer of receivables guaranteed by inheritance. Second, the obstacles faced by the creditor associated with the transfer of rights to the inheritance land that is still burdened by the Mortgage Rights is the obstacle in the process behind the name to the heirs in the Land Office. Thirdly, the rejection of the heirs over the inheritance of land rights that are in the imposition of the Deposit Rights does not result in the Deposit Rights being burdened to be abolished